Recent Advances in Computational Optimization Results of the Workshop on Computational Optimization WCO 2016 - Fidanova, Stefka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents new optimization approaches and methods and their application in real-world and industrial problems, and demonstrates how many of the problems arising in engineering, economics and other domains can be formulated as optimization problems. Constituting a comprehensive collection of extended contributions from the 9th International Workshop on Computational Optimization (WCO) held in Gdansk, Poland, September 11-14, 2016, the book discusses important applications such as job scheduling, wildfire modeling, parameter settings for controlling different processes, capital budgeting, data mining, finding the location of sensors in a given network, identifying the conformation of molecules, algorithm correctness, decision support system, and computer memory management. Further, it shows how to develop algorithms for these based on new intelligent methods like evolutionary computations, ant colony optimization and constraint programming. The book is a valuable resource for researchers and practitioners alike.
Sequential Predictive Scheduling in Partitioned Data Domains -- Wildﬁre Optimizations in Modeling and Calibrations for Bulgarian Test Cases -- Process Control with the Variability Constraints -- Comparison of Diﬀerent ACO Start Strategies Based on InterCriteria Analysis -- Evolutionary Approach for Tuning of Longwall Scraper Conveyor Model -- Solving Graph Partitioning Problems with Parallel Metaheuristics -- Comparison of Selected Fuzzy PSO Algorithms.
Keywords: Computational intelligence; Artificial intelligence; Mathematical optimization; Computational Intelligence; Artificial Intelligence; Optimization